Pengaruh Role Play Bantuan Hidup Dasar terhadap Peningkatan Pengetahuan Masyarakat Pesisir dalam Penanganan Korban Tenggelam - Idham Soamole; Windarti Rumaolat; Hasna Tunny (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Coastal communities as the first rescuers to provide assistance to drowning victims, it is necessary to understand basic life support for handling drowning victims, this is to prevent mistakes, thus it is necessary to provide counseling by means of role-play regarding basic life assistance. Increase the knowledge of coastal communities in handling drowning victims with the role-play counseling method for basic life support. This research is quasi-experimental with a one-group pretest-posttest design. The sample is ordinary people living in coastal areas with 30 respondents selected by purposive sampling. The instrument uses questionnaires, leaflets, and power points containing basic life support material. Statistical management uses the Paired Sample T-Test with a significance level of ( 0.05). This study found that the p-value = 0.000 with (α <0.05), meaning that there is an influence of the role-play counseling method on increasing the knowledge of coastal communities in handling drowning victims. Providing counseling using the role-play method is very efficient in increasing knowledge of basic life support for coastal communities in handling drowning victims.